PERANCANGAN USULAN UNTUK MENINGKATKAN INTENSI PENGGUNA JAM TANGAN TRADISIONAL DALAM BERALIH KE SMARTWATCH - Chaerunissa, Zabina
Smartwatches, a form of wearable technology resembling traditional watches, are now widely produced and sold in Indonesia. However, the intention to use smartwatches among traditional watch users is still considered low. This indicates that there are barriers to adopting this technology. Therefore, to increase the intention to switch to smartwatches, a study was conducted to identify the factors influencing the switching intention of traditional watch users to smartwatches and to design solutions based on the factors that directly affect the intention to switch.